Coding and Artificial Intelligence (AI) learning in teachers' perspective - Mirlanda Diaz Pratiwi; Asep Herry Hernawan; Ahmad Fajar Fadillah (Curricula: Journal of Curriculum Development, 2025)
Technological advancements have brought about changes to the curriculum, particularly the integration of coding and Artificial Intelligence (AI) into learning. This study aims to explore teachers' perspectives on coding and AI learning policies in the Kurikulum Merdeka, focusing on the factors that influence the adoption and acceptance of technology. The research was conducted using a qualitative approach, using in-depth interviews with six teachers from elementary, junior high, high school, and vocational school levels in Bandung City. The analysis framework utilizes the Unified Theory of Acceptance and Use of Technology (UTAUT) theory, which encompasses four key constructs: performance expectancy, effort expectancy, social influence, and facilitating conditions. The results indicate that teachers have positive expectations regarding the benefits of learning coding and AI. However, challenges persist in terms of infrastructure readiness, training, and institutional support. Perceived ease of use and social influence varied depending on the level and type of school. The research conclusion reveals that, although teachers in Bandung City generally exhibit a positive attitude towards coding and AI learning in the Kurikulum Merdeka, the level of implementation readiness remains unequal across educational units, necessitating contextual and adaptive policies.    Abstrak Perkembangan teknologi telah membawa perubahan pada kurikulum, khususnya masuknya koding dan Kecerdasan Artifisial (KA) dalam pembelajaran. Penelitian ini bertujuan untuk menggali perspektif guru terhadap kebijakan pembelajaran Koding dan KA dalam Kurikulum Merdeka, dengan fokus pada faktor-faktor yang mempengaruhi adopsi dan penerimaan teknologi. Penelitian dilakukan dengan pendekatan kualitatif menggunakan metode wawancara mendalam kepada enam guru dari jenjang SD, SMP, SMA, dan SMK di Kota Bandung. Kerangka analisis menggunakan teori Unified Theory of Acceptance and Use of Technology (UTAUT), mencakup empat konstruk: performance expectancy, effort expectancy, social influence, dan facilitating conditions. Hasil penelitian menunjukkan bahwa guru memiliki ekspektasi positif terhadap manfaat pembelajaran Koding dan KA, namun masih terdapat tantangan dalam hal kesiapan infrastruktur, pelatihan, dan dukungan institusional. Persepsi kemudahan penggunaan dan pengaruh sosial bervariasi tergantung pada jenjang dan jenis sekolah. Kesimpulan penelitian menunjukkan bahwa meskipun guru di Kota Bandung secara umum menunjukkan sikap positif terhadap pembelajaran koding dan KA dalam Kurikulum Merdeka, tingkat kesiapan implementasi masih timpang antar satuan pendidikan sehingga diperlukan kebijakan yang kontekstual dan adaptif. Kata Kunci: kecerdasan artifisial; koding; perspektif guru; UTAUT